Self studies the psychology of self and identity - Scheibe, Karl E. 1937- (Westport, Connecticut Praeger Publishers, an imprint of Greenwood Publishing Group, Inc., 1995)
In this far-ranging study, Scheibe seeks an understanding of the self and personal identity. In doing so, he focuses on the various relationships of the self in social environments. He examines the major historical perspectives on the self, the process or processes of socialization, memory, and identity, and the psychology of national identity. A well-written look at the essential considerations affecting the self in its development, ongoing and changing identity, and its relationships to others and to institutions, this study will be of interest to scholars and researchers in psychology and sociology as well as the general reader.
Preface -- Psyche and the socius: being and being in-place -- Historical perspectives on the presented self -- Socialization: the formation on the presented self -- The transvaluation of social identity -- The psychology of national identity -- Memory, identity, and history -- Fugitive identity, self-control, and the spy -- Self-narratives and adventure -- Legitimized aggression and the assignment of evil.
Includes bibliographical references (pages [205]-216) and index.
Keywords: Social psychology; Group identity; Identity (Psychology); Self